Geochemical Characteristics of Groundwater Consumed by Patients with Chronic Kidney Disease with Unknown Aetiology in the Crystalline Dry Zone Terrain of Sri Lanka - Chandrajith, Rohana; Nanayakkara, Nishantha; Zwiener, Christian; Daniel, Christoph; Amann, Kerstin Ute; Barth, Johannes (Exposure and Health, 2023)
Quality of drinking water has become a significant concern with chronic kidney disease of uncertain aetiology (CKDu), particularly in the dry zone regions of Sri Lanka. In this study, groundwaters consumed by biopsy-proven CKDu patients were assessed for identifying possible hydrogeochemical risk factors because histopathological observations are still considered the best method for identifying CKDu cases. Major anions, cations, and 22 trace elements in groundwater were measured in addition to dissolved organic carbon (DOC) and its isotope ratios (expressed as δ13CDOC). Variations of groundwater quality were monitored monthly in five selected wells. The data were compared with a non-endemic region with a similar climatic and socio-economic background. Groundwater used by CKDu cases is predominantly of the Ca–Mg–HCO3 type. Over 88% of the samples showed excess hardness, while 44% showed high fluoride (F−) contents (> 0.60 mg/L). These two parameters are noticeably different compared to groundwater from non-endemic regions with similar geoenvironmental backgrounds. The dissolved organic carbon (DOC) content varied from 0.06 to 0.30 mmol/L with a mean value of 0.15 mmol/L in CKDu wells. In most cases, known nephrotoxic trace elements such as As, Pb, Cd, and U were found to be lower than 0.01 µg/L. Seasonally, F− and Si4+ (as H4SiO4) content fluctuated, even though monsoon rain inputs did not seem to alter the geochemical composition. Principal component analysis (PCA) indicated that the dissolution of aquifer minerals and ion exchange processes are most likely responsible for the groundwater geochemistry in the study terrain. This study highlights the importance of F−, hardness (Ca2+ + Mg2+), and Si4+ in groundwaters of CKDu-related tropical terrains. The synergetic impact of these parameters needs further systematic studies, ideally combined with animal models, to unravel the aetiological mechanisms of CKDu.
CRIS-Team Scopus Importer:2023-04-14
Keywords: CKDu; Dissolved organic carbon; Environmental-nephrotoxin; Fluoride; Silica; Water hardness; Water isotopes